CLASSROOM MANAGEMENT FOR IMPROVING CHILDREN'S LITERACY - Adriyani, Adriyani; Darmiyati, Darmiyati; Halimatussadi’yah, Halimatussadi’yah (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The low ability to recognize children's early literacy, low children's learning activities and low focus on learning activities that make children lack learning motivation and lack of desire to excel in a learning activity should be a concern in this study. The purpose is to analyze teacher activities, children's activities and literacy development results using sand media in Kenanga Banjarmasin Kindergarten. This research use Classroom Action Research with qualitative and quantitative approaches used in this study. It is conducted in three meetings with children from group A of Kenanga Banjarmasin Kindergarten, with a total of 8 children. The results showed that teacher activity always increased in every meeting starting from the 1st meeting obtaining a score of 26 with Good criteria, until the 3rd meeting obtaining a score of 34 with Very Good criteria. Child activity 1st meeting with 38% Active criteria, 2nd meeting with 75% Active criteria and 3rd meeting with 100% Very Active criteria. The results of child literacy development at the last meeting reached 100%. It was concluded that the combination of Project Based Learning, Mastery Learning, Number Head Together models using sand media was proven to develop children's activities and children's literacy development outcomes. It is recommended that principals, educators and subsequent analysis can be material to further develop learning in children.